Best practices for teaching social studies : what award-winning classroom teachers do - Stone, Randi (b, 2015)
This collection of outstanding, teacher-tested methods for K12 social studies instruction for diverse classrooms offers fresh ideas and strategies covering citizenship, diversity, community, and more
Includes index.
Keywords: Social sciences -- Case studies. -- Study and teaching -- United States; Effective teaching -- Case studies. -- United States